Using the consolidated framework for implementation research (CFIR) to guide implementation of cardio‐oncology services - Jessica Miller Clouser; Colleen A. McMullen; Akosua K. Adu; Gretchen Wells; Amit Arbune; Jing Li (Wiley, 2024)
Abstract Introduction Cardio‐oncology focuses on diagnosing and preventing adverse cardiovascular outcomes in cancer patients. Interdisciplinary cardio‐oncology services address the spectrum of prevention, detection, monitoring, and treatment of cancer patients at risk of cardio‐toxicity and aim to improve the continuum of cardiac care for oncology patients. The goal of this study was to engage clinician and administrative stakeholders to assess multilevel needs, barriers, and expectations regarding cardio oncology services. Methods We interviewed clinicians and administrators at an academic medical center using the Consolidated Framework for Implementation Research (CFIR) to understand multilevel determinants influencing cardio‐oncology service implementation. We also conducted a web‐based survey to assess the knowledge, attitude, and perceptions of cardio‐oncology services held by local and regional clinicians who may refer cardio‐oncology patients to the study site. Results Multiple facilitators to cardio‐oncology service implementation emerged. Interview participants believed cardio‐oncology services could benefit patients and the organization by providing a competitive advantage. A majority (74%) of clinicians surveyed thought a cardio‐oncology service would significantly improve cancer patients' prognoses. Implementation barriers discussed included costs and a siloed organizational structure that complicated cross‐service collaboration. In the clinician survey, differences in the views toward cardio‐oncology services held by cardiology versus oncology providers would need to be negotiated in future cardio‐oncology service development. For example, while most providers accepted similar risk of cardio‐toxicity when consenting patients for cancer therapy in a curative setting, cardiologists accepted significantly higher levels of risk than oncologists in an incurable setting: 75% of oncologists accepted 1‐5% risk; 77% of cardiologists accepted ≥5% risk). Conclusions Participants supported implementation and development of cardio‐oncology services. Respondents also noted multi‐level barriers that could be addressed to maximize the potential for success. Engaging administrators and clinicians from cardiology and oncology disciplines in the future development of such services can help ensure maximal relevance and uptake.